Progress in the Application of Resting-State Functional Magnetic Resonance Imaging in Chronic Nonspecific Low Back Pain - XU Ting; XUE Qin; LÜ Ying; TU Jianchun; DAI Dechun (康复学报)
Chronic Nonspecific Low Back Pain (CNLBP) is one of the common diseases in orthopedics and rehabilitation medicine. The high incidence, recurrence rate, and disability rate of CNLBP prompt continuous exploration of its pathophysiological mechanisms. Resting-state functional magnetic resonance imaging (rs-fMRI) can reflect the intensity of neuronal activity to acertain extent and has unique advantages in the study of central mechanisms of CNLBP. Variousmethods are used for rs-fMRI analysis, mainly including functional segregation and integration. Common methods for functional segregation mainly include Amplitude of Low-Frequency Fluctuations (ALFF) and Regional Homogeneity (ReHo). Common methods for functional integration mainly include Seed-based Functional Connectivity Analysis (SCA), Independent Component Analysis (ICA), and graph theory-based complex brain network analysis. These methods have their own characteristics and also have corresponding limitations. This paper reviews the specific applications of various rs-fMRI analysis methods in the study of central mechanisms of CNLBP and discusses and prospects the current research status, hoping to provide reference for the study of neural mechanisms of CNLBP. Studies show that there are plastic changes in the brain areas related to pain perception, emotion, and cognition in CNLBP, and these abnormalities still exist even in the absence of noxious pain; the function of the motivation-reward circuit in CNLBP is weakened, leading to a decline in cognitive ability; the Default Mode Network (DMN) produces complex regulation of pain through the adjustment within its own network and other brain networks; negative emotions may further reduce the information transmission capacity at both global and local levels of the CNLBP brain functional network. Dynamic rs-fMRI analysis methods provide supplementary information on the conduction and integration regulation of pain information within the brain, which may be more suitable for explaining the complex and dynamic characteristics of pain, providing a new perspective for exploring the central neural mechanisms of CNLBP, and may be the direction of future research.